Cryopreservation of neural crest-derived cells - Bozhok, Galyna; Ustychenko, Viktoriya; Sydorenko, Olga; Bozhkova, Yuliya; Alabedalkarim, Nataliya; Pakhomov, Oleksandr; Vvedenskyi, Dmytro; Shatillo, Andriy; Bondarenko, Tetyana; Legach, Yevgen (Problems of Cryobiology and Cryomedicine, 2025)
Neural crest-derived cells are formed from neuroectoderm at early stages of embryogenesis. As a result of the epitheliomesenchymal transition, they migrate to peripheral structures and differentiate into neurons and glia of the peripheral nervous system, skin melanocytes, dental pulp cells, neuroendocrine cells, cartilage and bones of the skull and several other phenotypes. Neural crest derivatives have great prospects for application in regenerative medicine. Cryopreservation is widely used for long-term storage of biological material, enabling its application in clinical practice. Here, we have avalyzed the approaches to cryopreservation of neural crest-derived cells procured from different sources. The in vitro and in vivo studies demonstrate the effectiveness of the developed protocols for cryopreservation of various neural crest-derived cells, which opens the way for establishing cryobanks and expanding the use of these cells in clinical practice. Probl Cryobiol Cryomed 2025; 35(1):3–13